Sm‐p80‐based vaccine trial in baboons: efficacy when mimicking natural conditions of chronic disease, praziquantel therapy, immunization, and Schistosoma mansoni re‐encounter. Issue 1 (11th June 2018) - Siddiqui, Arif J.; Molehin, Adebayo J.; Zhang, Weidong; Ganapathy, Pramodh K.; Kim, Eunjee; Rojo, Juan U.; Redman, Whitni K.; Sennoune, Souad R.; Sudduth, Justin; Freeborn, Jasmin; Hunter, Derick; Kottapalli, Kameswara R.; et al.
Abstract: Sm‐p80‐based vaccine efficacy for Schistosoma mansoni was evaluated in a baboon model of infection and disease. The study was designed to replicate a human vaccine implementation scenario for endemic regions in which vaccine would be administered following drug treatment of infected individuals. In our study, the Sm‐p80‐based vaccine reduced principal pathology producing hepatic egg burdens by 38.0% and egg load in small and large intestines by 72.2% and 49.4%, respectively, in baboons. Notably, hatching rates of eggs recovered from liver and small and large intestine of vaccinated animals were significantly reduced, by 60.4%, 48.6%, and 82.3%, respectively. Observed reduction in egg maturation/hatching rates was supported by immunofluorescence and confocal microscopy showing unique differences in Sm‐p80 expression in worms of both sexes and matured eggs. Vaccinated baboons had a 64.5% reduction in urine schistosome circulating anodic antigen, a parameter that reflects worm numbers/health status in infected hosts. Preliminary analyses of RNA sequencing revealed unique genes and canonical pathways associated with establishment of chronic disease, praziquantel‐mediated parasite killing, and Sm‐p80‐mediated protection in vaccinated baboons. Overall, our study demonstrated efficacy of the Sm‐p80 vaccine and provides insight into some of the epistatic interactions associated with protection. Abstract : We demonstrate that Sm‐p80 + CpG‐ODN vaccination of Baboons results in marked protection against Schistosoma mansoni tissue egg burden and a significant reduction of viability and hatching rates of eggs. These data, together with our previously published reports on Sm‐p80‐based vaccine efficacies, support the continued development of Sm‐p80 for human clinical trials scheduled to start in 2019.